Legal Politics on the Regulation of Obligations to Hold General Meeting of Shareholders in Law Number 40 of 2007 concerning Limited Liability Companies - Yusman, Yusman; Rezki, Annissa; Yunus, Nur Rohim (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
The implementation of the General Meeting of Shareholders (GMS) has been regulated in law number 40 of 2007 concerning Limited Liability Companies. However, it should be noted that in the implementation there are two implementations that must be considered, namely the implementation of an open and closed GMS, each of which has differences and its own rules. In addition, the implementation of the GMS if it can be done in the form of a teleconference which has different points of view from several parties. It should also be noted that the implementation of General Shareholders (GMS) has weaknesses and strengths that must also be known as stated in law number 40 of 2007 concerning Limited Liability Companies. In this paper, the author uses descriptive qualitative research methodology in order to make it easier for the author to explain about the implementation of the General Meeting of Shareholders (GMS) considering that this knowledge is indispensable for law students in particular and parties from government and private agencies as one of the ingredients. writing and research in general.Keywords: GMS, Limited Liability Company, Company Law, Media TeleconferenceÂ AbstrakPelaksanaan Rapat Umum Pemegang Saham (RUPS) sudah diatur dalam undang-undang nomor 40 tahun 2007 tentang Perseroan Terbatas. Namun perlu diketahui dalam penyelenggaraannya terdapat dua pelaksanaan yang harus diperhatikan, yaitu pelaksanaan RUPS terbuka dan tertutup yang masing-masingnya terdapat perbedaan dan aturannya sendiri. Selain itu, pelaksanaan RUPS jika bisa dilakukan dalam bentuk teleconference yang memiliki sudut pandang berbeda dari beberapa pihak. Dan perlu diketahui juga bahwa pelaksaan Umum Pemegang Saham (RUPS) memiliki kelemahan dan kelebihan juga yang harus diketahui juga seperti yang disebutkan dalam undang-undang nomor 40 tahun 2007 tentang Perseroan Terbatas. Dalam penulisan ini, penulis menggunakan metodologi penelitian kualitatif deskriptif guna untuk lebih memudahkan penulis untuk menjelaskan tentang Pelaksanaan Rapat Umum Pemegang Saham (RUPS) mengingat pegetahuan ini sangat diperlukan bagi kalangan mahasiswa hukum secara khususnya dan pihak-pihak dari instansi pemerintah maupun swasta sebagai salah satu bahan tulisan maupun penelitian pada umumnya.Kata Kunci: RUPS, Perseroan Terbatas, UUPT, Media Teleconference